2015
DOI: 10.4172/2155-9546.1000324
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Fishmeal by Poultry By-Product Meal in Formulated Diets for Growing Hatchery–Reared Juvenile Spotted Babylon (Babylonia areolata)

Abstract: A feeding trial was conducted to evaluate the effects of five levels of partial to total replacement of fishmeal by poultry by-product meal on growth performance and body composition of hatchery-reared juvenile spotted babylon (Babylonia areolata) under aflow-through culture system over 150 days. Five experimental diets were formulated to contain 0%, 25% 50%, 75% and 100% of gradient poultry by-product meal (diet PBM0, PBM25, PBM50, PBM75 and PBM100, respectively). Significant differences (P<0.05) in weight ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Fish fed with D30 and D50 showed a significantly greater amount of body lipid and lower ash content, in comparison with those of fish fed coppens and D0. This trend was similar to that related in the earlier studies of Kristsanapuntu et al [76] in red drum, Sciaenops ocellatus, and [32] in catfish Clarias batrachus. According to Luchtman et al [32], the increased body lipid content may be due to increased energy content of diets containing MFV meal, which have a greater fat content ( Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…Fish fed with D30 and D50 showed a significantly greater amount of body lipid and lower ash content, in comparison with those of fish fed coppens and D0. This trend was similar to that related in the earlier studies of Kristsanapuntu et al [76] in red drum, Sciaenops ocellatus, and [32] in catfish Clarias batrachus. According to Luchtman et al [32], the increased body lipid content may be due to increased energy content of diets containing MFV meal, which have a greater fat content ( Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…Aquaculture development in the world depends largely on the availability of fish feed: aquafeed for intensive aquaculture is based on fish meal as the main protein source. To achieve a good growth, catfish requires complete artificial feed of 35 -45% protein level [2,11,13]. Fishmeal is a major protein component in formulated aquaculture feeds also for catfishes, its use in African catfish formulated feed is 40 to 60%.…”
Section: Resultsmentioning
confidence: 99%
“…One of promising species is African catfish (Clarias gariepinus). It is a globally popular cultured fish in Africa, Asia and Europe [11,12]. It is widely cultured infreshwater ponds, tanks.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies concluded that animal protein components can be valuable for fish feed formulation. They are rather much less expensive than fish meal (Hernandez et al, 2014;Sierra et al, 2014;Kritsanapuntu and Chaitanawisuti, 2015;Yu et al, 2015;Yones and Metwalli, 2015).…”
Section: Terrestrial Animal By-productsmentioning
confidence: 99%